POLEMIKA MAKSYMA GORKIEGO Z KADETAMI I BOLSZEWIKAMI NA ŁAMACH GAZETY „NOWAJA ŻYZŃ" - Głuszkowski, Piotr (Acta Neophilologica, 2019)
In the years 1917-1918 Maxim Gorky published a series of articles “Untimely thoughts” with a subtitle “Revolution and culture” in the “Novaya Zhizn” (New Life) newspaper, in which he appealed for finishing the war and strengthening the position of workers. He also protested against Kerensky’s dictatorship and warned against the peasantry barbarity. The K-D newspaper “Rech” (Speech), defending the policy of the Russian Provisional Government, entered into polemics with Gorky. Since the October Revolution the main opponent of “Novaya Zhizn” had been the bolshevist “Prav-da” (The Truth). Gorky accused Bolsheviks of betraying the revolution and criticised their policy of terror.